Differential Regulation of an OsIspH1, the Functional 4-Hydroxy-3-Methylbut-2-Enyl Diphosphate Reductase, for Photosynthetic Pigment Biosynthesis in Rice Leaves and Seeds - Lee, Yeo Jin; Kim, Jae Kwang; Baek, Seung-A; Yu, Ji-Su; You, Min Kyoung; Ha, Sun-Hwa (Frontiers in Plant Science, 2022)
The methylerythritol 4-phosphate (MEP) pathway is responsible for providing common precursors for the biosynthesis of diverse plastidial terpenoids, including chlorophylls, carotenoids, and phytohormones, in plants. In rice (Oryza sativa), the last step genes encoding 4-hydroxy-3-methylbut-2-enyl diphosphate reductase (HDR/IspH) have been annotated in two genes (OsIspH1 and OsIspH2) in the rice genome. The spatial transcript levels indicated that OsIspH1 is highly expressed in all tissues at different developmental stages, whereas OsIspH2 is barely expressed due to an early stop in exon 1 caused by splicing error. OsIspH1 localized into plastids and osisph1, a T-DNA inserted knock-out mutant, showed an albino phenotype, indicating that OsIspH1 is the only functional gene. To elucidate the role of OsIspH1 in the MEP pathway, we created two single (H145P and K407R) and double (H145P/K407R) mutations and performed complementation tests in two hdr mutants, including E. coli DLYT1 strains and osisph1 rice plants. The results showed that every single mutation retained HDR function, but a double mutation lost it, proposing the complementary relations of two residues might be important for enzyme activity, but not each residue. When overexpressed in rice plants, the double-mutated gene, OsIspH1MUT, reduced chlorophyll and carotenoid biosynthesis in the leaves and seeds. It confirmed the crucial role of OsIspH1 in plastidic terpenoid biosynthesis, revealing organ-specific differential regulation of OsIspH1 in rice plants.